Protoype Pengembangan Ion Generator Dengan Teknologi Inverter - Nadia Amira Putri; UPIK ARI ERLITA (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2023)
Clean air is the main human need to support the health of the body so that it can be active with a fit body condition. One of the ingredients in the air is positive and negative ions. But research says that the ions that are good for health are negative ions, negarif ions themselves are usually found in waterfalls, mountains, or beaches. For people who live in urban areas is very difficult to get clean air, because urban air is polluted. Pollutants can also occur in closed rooms. and likely to have a greater impact on health than outdoor pollution. This study aims to create a prototype tool development of ion generator with inverter technology. This study uses an Ion Generator as a producer of negative ions controlled by arduino microcontroller, Dust Sensor (Gpy2y1010au0f) to detect pollutants in the room, LCD (Liquid Crystal Display) as a digital display used to display pollutants detected on the sensor, Buzzer as an indicator when the sensor detects excess pollutants. The results of the kuesioner of material experts obtained 87% and media experts get 84%, which means this tool is very good to use.